Designing fusion molecules from antigens of Mycobacterium tuberculosis for detection of multiple antibodies in plasma of TB patients. (September 2020) - Akhter, Mohsina; Arif, Shaista; Khaliq, Aasia; Nisa, Zaib un; Khan, Imran H.; Akhtar, Muhammad Waheed
Abstract: Tuberculosis (TB) is amongst the deadliest diseases worldwide. For effective control of TB a rapid, reliable and sensitive method for its diagnosis is essential. Serodiagnosis detecting multiple antibodies against antigens of Mycobacterium tuberculosis ( Mtb ) in blood samples could prove beneficial. Based on the epitope position in the molecule, two truncated variants of Rv1984c, i.e., Tn1Rv1984c and Tn2Rv1984c were expressed in Escherichia coli. Screening of the Rv1984c, Tn1Rv1984c and Tn2Rv1984c against 231 sera samples from the culture positive TB patients showed sensitivities of 34.2%, 49.4% and 26.8%, respectively. Another antigen Rv1352 was analyzed for the location of epitopes, which had not been reported before. A fusion molecule consisting of Tn1Rv1984c and Rv1352, expressed in E. coli, showed enhanced sensitivity of 62.8%. Joining another antigen Rv2031c to the N-terminus of Tn1Rv1984c-Rv1352, improved sensitivity to 71.4%. The fusion construct Rv2031c-Tn1Rv1984c-Rv1352 showed comparatively higher sensitivity of 73.4% in the male group as compared to 67% in the female group. Data derived for the secondary structure analysis through Circular Dichroism (CD) spectroscopy and prediction on the basis of molecular modelling was also in agreement. This construct can be a potential base for producing constructs with greater sensitivity through fusion of epitopes from additional Mtb antigens. Highlights: Unmasking of the epitopes in the truncated Mtb antigen Rv1984c resulted in 44% increase in sensitivity. Three B-Cell epitopes of the Rv1352 were predicted for the first time on the basis of in-Silico prediction tools. The fusion construct Rv2031c-Tn1Rv1984c-Rv1352 can be a promising base for constructing molecules with high sensitivity.